Assessment of soluble protein and collagen characteristics of dry-aged beef from Angus × Thai native and Charolais × Thai native crossbred steers - Saleepochn, Tharinee; Chavanasilp, Phodchara; Kanram, Pachara; Kityakarn, Sutasinee; Pantu, Piboon; Pongprayoon, Prapasiri; Suwanasopee, Thanathip; Jattawa, Danai; Luksirikul, Patraporn; Koonawootrittriron, Skorn (Agriculture and Natural Resources, 2024)
Importance of the work: The rising demand for premium beef necessitates more comprehensive indicators, in addition to traditional traits, to evaluate meat quality. Objectives: To assess the meat quality of dry-aged steaks from crossbred cattle, focusing on soluble protein and collagen as supplementary indicators. Materials and Methods: Dry-aged steaks from two crossbred cattle breeds were analyzed for soluble protein and collagen. Rib eye (longissimus thoracis) and strip loin (longissimus lumborum) cuts were compared from the cattle raised under normal and overfeeding conditions. The study examined the relationship between these components and conventional meat quality traits such as pH, cooking loss and shear force. Results: Dry-aged beef steaks were examined from two cattle crossbreeds (Angus and Charolais with Thai native) raised under normal and overfeeding conditions. The soluble protein components were affected by both breed type and feeding condition. Additionally, there were significant differences in the sarcoplasmic protein and collagen contents between the two studied beef cuts that the tested conventional meat quality traits (pH, cooking loss and Warner-Bratzler shear force) could not differentiate. Main finding: The soluble protein and collagen contents could serve as supplementary indicators for evaluating meat quality and offer a more nuanced assessment than using conventional methods. Further research is necessary to clarify the correlation between these chemical components, complex muscle characteristics and sensory quality.